Penguatan Pendidikan Karakter Berbasis Masyarakat pada Sekolah Menengah Pertama Negeri (SMPN) di Kabupaten Tulang Bawang Provinsi Lampung - hasan, Yetri; Firdaos, Rijal (Universitas Islam Negeri Raden Intan Lampung, 2017)
This research aims to see the school's efforts in strengthening community-based character education, especially related to how to build participation and collaboration between schools and communities in the successful implementation of character education strengthening with school extracurricular activities. Research This is Qualitative research as this study uses a natural setting , with the aim of interpreting phenomena that occur and are carried out by means of involving several existing methods. In conducting data collection, this study uses FGD, interviews and observations. The next data is processed quantitatively from the results of the study. First; that the ability of schools to build collaboration and involvement of the community in KDP, still faces various obstacles and can be categorized as not optimal. Second; in general the community is enthusiastic about welcoming the KDP program, and has the willingness to actively participate in participating in the success of the KDP program. Third; schools have not yet discovered the design activities or design implementation that fits the needs of the school (interests, talents, abilities and creativity of the school and local wisdom in the school environment). And fourth; the design model for KDP implementation through extracurricular activities offered in this study is still a basic model, which can be adopted and modified by schools that adjust the school conditions, willingness and readiness of the community.